Male mating performance and cytoplasmic incompatibility in a wPip Wolbachia trans‐infected line of Aedes albopictus (Stegomyia albopicta). Issue 4 (22nd November 2012) - MORETTI, R.; CALVITTI, M.
Abstract : Wolbachia pipientis Hertig (Rickettsiales: Rickettsiaceae) is a maternally inherited endosymbiont of a large number of insects and other arthropods that induces various effects on host reproductive biology. Among these, cytoplasmic incompatibility (CI) is a form of sterility induced in eggs produced by mating between infected males and females uninfected or infected by an incompatible Wolbachia strain. This phenomenon has been proposed as a potential way to produce functionally sterile males to be used in genetic control programmes. In this paper, we report on experiments carried out to evaluate the mating performances of males of an Aedes albopictus ( Stegomyia albopicta ) (Diptera: Culicidae) line (AR w P), harbouring a new Wolbachia infection [the w Pip strain from Culex pipiens Linnaeus (Diptera: Culicidae)], in comparison with naturally infected males (SR line). AR w P males did not differ from SR males with regard to insemination capacity. Mating competitiveness did not differ significantly between lines in either laboratory or greenhouse conditions. Moreover, crosses with SR females were characterized by a 100% CI regardless of AR w P male age. All of these findings suggest that AR w P males may represent a very efficient tool for control programmes against Ae. albopictus based on the release of functionally sterile males.